DISEÑO DE UN SISTEMA DE CONTROL DE INVENTARIO Y ORGANIZACIÓN DE LAS BODEGAS DE PRODUCTO EN EL CENTRO COMERCIAL: "SU ECONOMÍA" SITUADO EN EL CANTÓN VALENCIA – PROVINCIA DE LOS RÍOS - Cedeño García, Karen Mayleth (2023)
The main objective of this research was to design a system that allows inventory control and the organization of product warehouses, in order to improve the management of products stored in the warehouses of the shopping center. In the Centro Comercial "Su Economía", as a company dedicated to the purchase and sale of mass consumer products, a survey was conducted with the administrative personnel to evaluate the current situation of product supply in order to identify the main problems affecting inventory management.